Development of android-based interactive learning media to improve student learning outcomes in class XII MIPA SMA - Armen Marta; Zelhendri Zen; Abna Hidayati; Ulfia Rahmi (Postgraduate, University of Mataram, 2025)
This research aims to develop android-based interactive learning media that meets the criteria of validity, practicality, and effectiveness for Mathematics class XII IPA. This media is expected to increase students' understanding, motivation, and independence in learning in order to achieve optimal learning outcomes. The method used is Research and Development with the ADDIE approach, which includes the stages of analyze, design, development, implementation, and evaluation. The main data sources came from validators, teachers, and students, analyzed descriptively to measure aspects of validity, practicality, and effectiveness of the media. The validation results showed a high level of feasibility, with a score of 98% for media aspects, 85% for materials, and 95% for language. The practicality of the media was also rated very high by 99% teachers and 94% students. The effectiveness test resulted in a gain score value of 0.68 categorized as high, and the t-test showed difference between the pre-test and post-test results (Sig. 0.000 <0.05), evidenced by a significant increase in the average student learning outcomes, from 67.00 to 90.00. Based on these findings, this interactive media is feasible to be used in learning mathematics class XII IPA SMA as a means to improve student learning outcomes.